Differences in Motor Competence by TV Consumption and Participation in Club Sports in Children Starting Elementary School - Klaus Greier; Clemens Drenowatz; Gerhard Ruedl; Carla Lackner; Klaudia Kroell; Veronika Feurstein-Zerlauth (Shiraz University of Medical Sciences, 2018)
Background: The development of motor competence during childhood has important implications for future health and well-being due to the association with physical activity. While associations between sports participation or TV time and motor competence have been examined previously, there remains limited research on the interaction of TV time and sports participation regarding motor competence. The present study; therefore, examines differences in motor competence by club sports participation and TV time in elementary-school children. Methods: 15 elementary schools in the federal state of Tyrol, Austria, were randomly selected for participation. Motor competence was assessed between October and December 2017 using the German Motor Test in 455 (49.5% boys) children starting elementary school. Body weight and height were measured with children in sports clothes and being barefoot following standardized procedures. In addition, parents reported participation and time spent in club sports (hours/week), as well as time spent watching TV (hours/day) via standardized questionnaires. Further, parents reported whether there was a TV in the child's bedroom. Differences in motor competence by sports participation and TV time were analyzed via multivariate analysis of variance. Results: In total, 24% of the participants exceeded the current recommendations for TV time (> 2 hours/day) and 46% participated in club sports. There was no difference in TV time and club sports participation between boys and girls. Nevertheless, boys displayed better standardized scores for flexibility (2.8 ± 0.8; P = 0.001), sprint (2.6 ± 0.9; P = 0.005), and sideways jumping (1.3 ± 0.6; P = 0.030) than girls. Significant interaction effects between TV time and club sports were observed for balance (P = 0.020), sit-ups (P = 0.039), endurance (P < 0.001), and overall motor competence (P = 0.035). In addition, club sports participation was associated with better performance on all motor competence tests (P-values ranging from 0.047 to < 0.001) while lower TV time was associated with better performance in sprint, sideways jumping, push-ups, 6-minute run, and total motor competence only (P-values ranging from 0.006 to < 0.001). Conclusions: Club sports participation appears to be an important contributor to the development of motor competence while high TV time may impair motor development, particularly in children not participating in club sports. Parents and educators; therefore, should facilitate participation in the organized physical activity even in pre-school children while limiting TV time.